Integration of electric vehicles in electricity-carbon market toward eco-transport futures - Wang, Zhidong; Yang, Fuyuan; Lai, Shuying; Tao, Yuechuan; Zhang, Jiawei (Frontiers in Smart Grids, 2025)
Integrating electric vehicles (EVs) into the electricity and carbon markets presents a promising pathway toward sustainable transportation futures. This article proposes a comprehensive framework that synergizes the operations of the electricity and carbon markets with the growing adoption of EVs. The proposed framework includes a low-carbon transmission network operation model that integrates the electricity and carbon markets, facilitating optimal energy dispatch while minimizing carbon emissions. In addition, the framework extends to distribution network operations, incorporating a double carbon taxation mechanism to address emissions at both the generation and consumption levels. A carbon emission flow model is employed to meticulously trace carbon emissions across the supply chain, enhancing transparency and accountability. The framework also introduces an EV-integrated traffic flow model that captures the interactions between transportation networks and energy demand, influencing traffic dynamics and EV charging behaviors. Furthermore, a planning and pricing model for EV charging stations is developed, incorporating carbon costs into the pricing strategy to incentivize eco-friendly practices. The multilevel solution algorithm ensures an iterative convergence of decision variables across transmission, distribution, and transportation networks, ultimately fostering an integrated eco-transport system. This work contributes to the development of sustainable transport systems by promoting efficient EV integration and supporting decarbonization efforts in both the energy and transportation sectors.